THE MOTIVATION COMPONENT OF LEGAL PROTECTION OF SOCIAL MORALS IN THE ACTIVITIES OF LAW ENFORCEMENT BODIES OF UKRAINE: CHALLENGES OF GLOBAL DEVELOPMENT OF SOCIETY - Ruvin, Sergiy (Socio-economic relations in the digital society, 2023)
The purpose of the article is to study the theoretical and legal discourse of the modern definition of the motivational component of the legal protection of public morality in the activity of law enforcement agencies of Ukraine. As a result of the conducted analysis, it is necessary to state that motivational orientation should be interpreted as a category of philosophical praxeology, which is most closely related to the concept of determination, and therefore, taking into account that motivation is an element and axiological, it is appropriate to emphasize the importance of confidence and conviction of a person in the correctness and reasonableness their own aspirations. This is possible provided there is a clear regulatory basis, especially when it comes to protocol and such responsible work as law enforcement. The article establishes that the motivation of a law enforcement officer closely interacts with legal deontology, which, by its very nature, determines the basic moral and social principles of interpersonal relations, which motivate in what way a law enforcement officer should understand his professional purpose, how exactly to interpret his mission, and, at most, to realize why the law enforcement profession exists at all. It was established that when investigating the motivational determination of the legal protection of public morality within law enforcement agencies, it is advisable to, first of all, talk about the implementation of the function of legal protection as a professional duty of representatives of law enforcement agencies, which follows from legal norms. It has been established that the problem of the relationship between public morality and the axiology of law enforcement activity is not only a complex topical question and a complex cognitive process, but, in fact, a new epistemological mechanism of scientific immersion in the ideological social foundations of the era of law enforcement system reforms, the era of revolutionary changes and, unfortunately, military realities of modern Ukraine. It is suggested that the motivational determination of the protection of public morality by law enforcement agencies, or their moral self-regulation, should be interpreted as a very comprehensive process, characterized by external and internal determinants, conditioned by the object of legal protection itself and dependent on the specifics of a specific law enforcement agency and its structural unit.